BLUMEMBERG, Hans. Naufrágio com espectador - Vieira, Andrea Luciana; Bueno, Cyntia Lacerda; Bastos, Evandro Alves; Neves, Fabiana Melo; Aguiar, José Otávio; Laurentys, Tereza Cristina de (Cadernos de História, 1999)
Resenha do Livro Naufrágio com Espectador de Hans Blememberg.